A Note on FC-Groups - Chernikov, N.S. (Український математичний журнал, 2003)
Let G be an arbitrary FC-group, let R be its locally soluble radical, and let L/R = L(G/R). We prove that, for N ⊲ G, G/N is residually finite if R ⊆ N ⊆ L. Нехай G — довільна FG-група, R — її локально розв'язний радикал і L/R=L(G/R). Доведено, що для N⊲G,G/N фінітно апроксимовна у випадку, коли R⊆N⊆L.